2016
DOI: 10.1371/journal.pone.0168418
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Toxin Is a Robust and Selective Inhibitor of High Grade Glioma Cell Migration and Invasion

Abstract: In high grade glioma (HGG), extensive tumor cell infiltration of normal brain typically precludes identifying effective margins for surgical resection or irradiation. Pertussis toxin (PT) is a multimeric complex that inactivates diverse Gi/o G-protein coupled receptors (GPCRs). Despite the broad continuum of regulatory events controlled by GPCRs, PT may be applicable as a therapeutic. We have shown that the urokinase receptor (uPAR) is a major driver of HGG cell migration. uPAR-initiated cell-signaling require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…After treatment with negative control (NC) siRNA or FPR2 siRNA, the monolayers of HUVECs were scratched linearly with a 200 μL pipette tip, and images of wounded monolayer were taken at 12 h. The results showed that FPR2 silencing decreased the migration of HUVEC cells compared to cells treated with NC siRNA. This indicates that FPR2 is correlated with the cell migration capacity of HUVECs, which is consistent with previous reports 54,55…”
Section: Resultssupporting
confidence: 93%
“…After treatment with negative control (NC) siRNA or FPR2 siRNA, the monolayers of HUVECs were scratched linearly with a 200 μL pipette tip, and images of wounded monolayer were taken at 12 h. The results showed that FPR2 silencing decreased the migration of HUVEC cells compared to cells treated with NC siRNA. This indicates that FPR2 is correlated with the cell migration capacity of HUVECs, which is consistent with previous reports 54,55…”
Section: Resultssupporting
confidence: 93%
“…It is thus intriguing that uPAR protein expression was substantially increased in U87 cells when these cells were cultured in neurospheres as opposed to monolayers. Similarly, uPAR protein expression was substantially increased when U87vIII cells were cultured in neurospheres 53 . These results may be interpreted to indicate that U87 and U87vIII cells that are capable of seeding neurospheres are uPAR-enriched.…”
Section: Discussionmentioning
confidence: 92%
“…The gene that encodes the EGF Receptor ( EGFR ) is over-expressed in up to 50% of all glioblastomas and in many of these tumors, EGFR is mutated to generate a constitutively active derivative called EGFRvIII 50 , 51 . U87 cells that express EGFRvIII are previously characterized and we previously demonstrated that these cells form neurospheres 52 , 53 . To determine whether activated EGFR signaling affects glioblastoma neurosphere formation, we prepared neurospheres with U87 and U87vIII cells under equivalent conditions.…”
Section: Resultsmentioning
confidence: 97%
“…The observation that the deletion of the Fpr1 gene reduced inflammation in an experimental mouse model of endometriosis [ 68 ] and that FPRs were mainly expressed on neutrophils and macrophages, suggests that these receptors predominantly govern a proinflammatory response which results in chemotaxis, degranulation, and oxidative burst during infection. The release of endogenous FPR ligands can influence severe diseases associated with inflammation, including systemic inflammatory response syndrome [ 69 ], Alzheimer′s disease, amyloidosis, prion disease, obesity, diabetes [ 70 ], and several types of cancer [ 71 , 72 , 73 , 74 ]. However, FPRs can also promote the resolution of inflammation.…”
Section: Introductionmentioning
confidence: 99%